Mini Bussiness Class Edupreneurship Anak TK Aisyiyah Bustanul Athfal 11 - Sudarni, Sri (Pena Edukasia, 2023)
Introducing the entrepreneurial spirit to children from an early age is a very good thing and has tremendous benefits for their future. To introduce and foster an entrepreneurial spirit cannot be done instantly and the formation of parents here is very supportive for the formation of the character of an entrepreneur in the future, in young children this is the right time and is an opportunity to learn the spirit of growing entrepreneurship, one of which is through informal education path. The purpose of this research is to examine how to build an entrepreneurial spirit in early childhood through the development of informal education and this research is only limited to fostering an entrepreneurial spirit in the family and their immediate environment. The aim of training entrepreneurship in children from an early age is to grow self-confidence, be independent and become people who have high creativity so that they become more productive when they grow up.